Upravljanje popolne odgovornosti kot pot do celovitega vodenja podjetja - Gorenak, Štefka (Naše gospodarstvo, 2010)
This contribution reports on the relationship and potential synergies between total quality (TQM) and total responsibility management (TRM). TQM and TRM are compared concerning their contribution to the holistic management of (innovative) enterprises. TRM principles and standards reflect the increasing public expectations about corporate social responsibility. Many companies are requiring the holistic development of TRM, thereby successfully managing their responsibilities toward their stakeholders and natural environments. The synergies between TRM and responsible consumption also lead (socially) responsible companies to long-term competitive advantages. Thus, the introduction of TRM may be a management innovation.
Keywords: management; podjetja; vodenje; poslovna strategija; odgovornost; inovativnost; družbena odgovornost; sustainable development; trajnostni razvoj